Nem tudo que parece é: as bibliotecas comunitárias caxienses e as suas relações com o poder público municipal - Silveira, João Paulo Borges da (My University, 2022)
Grounded in the field of Education and in dialogue with Librarian Science, this doctoral dissertation studies community libraries from the perspective of spaces for social transformation in the bias of non-formal education. The research problem aims to answer the following question: What are the potentialities of educational practices developed in community libraries for the place, especially in promoting the autonomy and citizenship of users and territories? Thus, the general goal was to analyze the potential of educational practices developed in community libraries related to access to reading and information, in the purpose of achieving autonomy and citizenship for users and territories in Caxias do Sul - Rio Grande do Sul. As a justification for the research, it is pointed out the need for access to reading and information in peripheral communities, especially in community libraries in Caxias. The theoretical framework is based on the concept of community libraries from authors such as Machado (2008; 2009), Fernandez & Machado (2016; 2018) and Castrillón (2018), and on the field of Education, Paulo Freire (1979; 1980; 2011; 2017a; 2017b) regarding the perspective of non-formal education and popular education. The sources used for analysis were documents produced by the Municipal Public Library of Caxias do Sul, interviews with public officials and reading agents, direct observation writing journal, legal documents and official publications on the City Hall website. Data analysis was based on Bardin's Content Analysis (2016), considering its four stages: organization, coding, categorization and inference. Until 2020, when the COVID-19 pandemic began, the city of Caxias do Sul had 17 community libraries in operation, three of which were investigated as case studies. The research revealed the influence of City Hall in the implementation of these libraries, from 2008 to 2016 all of them were created by the government and not by the communities themselves, as should happen in the case of community libraries. The relationship established between the government and the facilities is one of dependence for their maintenance, approaching a bond of subordination, in which the City Hall is sometimes placed as the creator and coordinator of community libraries, sometimes only as a provider of technical assistance. The official discourse assumes a partnership relationship from 2008 onwards, but this study reveals that the intentions of creating spaces predate the beginning of this action, coming from the 1990s, and the Municipal Culture Plan (2011) conveys the intention of the public power to absorb and take over the units in its library network. This study considers that community libraries in Caxias are neighborhood public libraries, neglected by the municipal government, which over the years, in different administrations since the installation of the first libraries, took different positions in relation to the initial project, which resulted in moments of distinct relationships, tensions and in the omission in the continuity of the service performed. [resumo fornecido pelo autor]
Alicerçada no campo da Educação e em diálogo com a Biblioteconomia, esta tese estuda as bibliotecas comunitárias na perspectiva de espaços de transformação social no viés da educação não-formal. O problema de pesquisa visa a responder a seguinte questão: Quais as potencialidades das práticas educativas desenvolvidas em bibliotecas comunitárias para o local, em especial, na promoção da autonomia e cidadania dos/as usuários/as e dos territórios? Neste caminho, o objetivo geral buscou analisar as potencialidades das práticas educativas desenvolvidas em bibliotecas comunitárias relacionadas ao acesso à leitura e à informação, para a conquista de autonomia e de cidadania aos/às usuários/as e dos territórios, em Caxias do Sul/RS. Como justificativa para a pesquisa aponta-se a necessidade de acesso à leitura e à informação em comunidades periféricas, em especial nas bibliotecas comunitárias caxienses. O referencial teórico apoia-se no conceito de bibliotecas comunitárias com Machado (2008; 2009), Fernandez e Machado (2016; 2018) e Castrillón (2018) e no campo da Educação na perspectiva da Educação não-formal e da Educação popular com Freire (1979; 1980; 2011; 2017a; 2017b). As fontes utilizadas para análise foram documentos produzidos pela Biblioteca Pública Municipal de Caxias do Sul, entrevistas realizadas com agentes públicos/as e agentes de leitura, escrita de diário de observação direta, documentos jurídicos e publicações oficiais do site da Prefeitura Municipal. O exame dos dados foi a partir da Análise de conteúdo, de Bardin (2016), considerando as suas quatro etapas: organização, codificação, categorização e inferência. A cidade de Caxias do Sul tinha até 2020, quando teve início a pandemia de COVID-19, 17 bibliotecas comunitárias em atividade, sendo que três foram investigadas como estudos de casos. A pesquisa revelou a influência da Prefeitura Municipal na implantação dessas bibliotecas, de 2008 a 2016, sendo todas criadas pelo poder público e não pelas próprias comunidades, como deveria acontecer em se tratando de bibliotecas comunitárias. A relação posta entre poder público e as unidades é de dependência para suas manutenções, se aproximando de vínculo de subordinação, em que a Prefeitura ora se coloca como criadora e coordenadora das bibliotecas comunitárias, ora apenas como prestadora de assessoria técnica. O discurso oficial supõe relação de parceria a partir de 2008, mas este estudo revela que as intenções de criação dos espaços são anteriores ao início dessa ação, vindo da década de 1990, sendo que o Plano Municipal de Cultura (2011) veicula a intenção do poder público de absorver e assumir as unidades em sua rede de bibliotecas. Este estudo considera que as bibliotecas comunitárias caxienses são bibliotecas públicas de bairro, negligenciadas pelo poder público municipal, que ao longo dos anos, em diferentes gestões desde a instalação das primeiras bibliotecas tomaram posturas diferentes em relação ao projeto inicial, o que acarretou momentos e relações distintas e de tensão e na omissão na continuidade do atendimento realizado. [resumo fornecido pelo autor]
Keywords: Bibliotecas - Caxias do Sul, RS; Educação popular; Política pública; Libraries - Caxias do Sul (Brazil); Popular education; Public policy